2022
DOI: 10.48550/arxiv.2210.17455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Refined magnetic structure of VI$_3$

Abstract: The van der Waals ferromagnet (FM), VI3, was studied by muon spin relaxation (µ + SR) and first principle calculations based on density functional theory (DFT). Temperature dependent zero field muon spin relaxation (µ + SR) measurements confirm the onset of long range FM order and the time spectra exhibits clear muon spin precession frequencies for T < TC = 50.03(1) K. The calculated internal magnetic fields at the predicted muon sites, based on the established magnetic structure from neutron diffraction, is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This is due to orbital quenching in a crystal field [36], making this option less probable. Indeed, even though orbital contributions of vanadium in octrahedral environment was in fact recently suggested in VI 3 by µ + SR and XAS [37,38], for NaCr 2 O 4 , an unusual mixed valance electronic state has instead been reported [8]. It was suggested that Na substitution in the solid solution Na x Ca 1−x Cr 2 O 4 does not result in electrons removed from the Cr site, as expected in typical mixed valence compounds.…”
Section: Discussionmentioning
confidence: 94%
“…This is due to orbital quenching in a crystal field [36], making this option less probable. Indeed, even though orbital contributions of vanadium in octrahedral environment was in fact recently suggested in VI 3 by µ + SR and XAS [37,38], for NaCr 2 O 4 , an unusual mixed valance electronic state has instead been reported [8]. It was suggested that Na substitution in the solid solution Na x Ca 1−x Cr 2 O 4 does not result in electrons removed from the Cr site, as expected in typical mixed valence compounds.…”
Section: Discussionmentioning
confidence: 94%